A study of menstrual hygiene practices and associated environmental & social factors among adolescent girls in rural Puducherry (One Health & Risk Management, 2023)
Introduction. Adolescent females were prevented from receiving the appropriate knowledge due to social restrictions and traditional beliefs, which in turn led to poor hygiene habits.Material and methods. A community-based descriptive cross-sectional study employing a semi-structured questionnaire was carried out in the rural field practice region of MGMCRI, Puducherry, between the 15th of March 2019 and the 31st of April 2021. The study was done in Puducherry. The comprehensive enumeration yielded a total of 528 countable teenage females.Results. The vast majority of the teenage females (89.2%) reported using sanitary pads, whereas just 6.6% and 4.2%, respectively, reported using fresh or reused towels. 65.3% of the girls changed their wet absorbent between two and five times during the day. The vast majority of the girls, or 60.8% of them, disposed of their spent absorbent by either burying it or burning it. 67.9% of the girls were cleansing their genitalia when they were urinating. 54.4% of people cleaned their hands using soap and water, whereas 1.4% utilized ash soil, muddy dirt, or other types of soil. There was a statistically significant correlation between the style of housing and the availability of sanitary latrines (p